Structural basis of Cullin-2 RING E3 ligase regulation by the COP9 signalosome - Faull, Sarah V; Lau, Andy; Martens, Chloe; Ahdash, Zainab; Yebenes, Hugo; Schmidt, Carla; Beuron, Fabienne; Cronin, Nora B; Morris, Edward P; Politis, Argyris (bioRxiv, 2018)
Cullin-Ring E3 Ligases (CRLs) regulate a multitude of cellular pathways through specific substrate receptors. The COP9 signalosome (CSN) deactivates CRLs by removing NEDD8 (N8) from activated Cullins. The structure of stable CSN-CRL can be used to understand this mechanism of regulation. Here we present the first structures of the neddylated and deneddylated CSN-CRL2 complexes by combining single particle cryo-electron microscopy (cryo-EM) with chemical cross-linking mass spectrometry (MS). These structures reveal a conserved mechanism of CSN activation, consisting of conformational clamping of the CRL2 substrate by CSN2/CSN4, release of the catalytic CSN5/CSN6 heterodimer and finally activation of the CSN5 deneddylation machinery. Using hydrogen deuterium exchange-MS we show that CRL2 binding and conformational activation of CSN5/CSN6 occur in a neddylation-independent manner. The presence of NEDD8 is required to activate the CSN5 active site. Overall, by synergising cryo-EM with MS, we identified novel sensory regions of the CSN that mediate its stepwise activation mechanism and provide a framework for better understanding the regulatory mechanism of other Cullin family members.